Comparison of DC Motor Speed Calculation Efficiency between Inductive Proximity Sensor and Rotary Encoder - Aryanto, Dino Dwi; Sukir, S. (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
This study examines the level of effectiveness and efficiency of a sensor on the calculation of the rotational speed (RPM) of a DC motor, considering that the calculation of the rotational speed of an electric motor, both AC motors and DC motors, greatly influences the output of the system. the speed of motor rotation is very influential in several fields, such as power generation, which will affect the output voltage that will be generated. There are many methods for measuring the rotational speed of a motor, including using an inductive proximity sensor and a rotary encoder combined with a PLC as a control center and data processor so that the rotational speed can be read. the output of the proximity sensor and rotary encoder will be connected to the PLC input pin so that data will appear in the form of a pulse value which can be seen in the program that has been made. The data obtained will be processed in a program that uses special instructions, namely PRV. In comparison, the speed of a dc motor will be changed using a PWM module or pulse width modulation to adjust the rotational speed of the motor. From the results of experiments that have been carried out using the proximity sensor, it gives an average motor speed reading of 6420 Rpm with an error of -10.3, and experiments carried out using a rotary encoder give an average motor speed reading of 6409.3 Rpm with an error of 0.4 so that it can be concluded that the use of a rotary encoder is more accurate than the use of a proximity sensor to calculate motor speed.